Research on Weight Lightening of 160 km/h Electric Locomotive Body - WANG Lu; XIAO Shoune; ZHU Tao; WANG Mingmeng; XU Deshan (机车电传动)
Taking 160 km/h electric locomotive body as lightweight goal, the finite element model for the locomotive body was builtand the static strength for the locomotive body was calculated. Considering the factors of structure strength and stiffness and taking theminimum total weight body as the goal and taking the plate thinkness parameters of body structure as design variables, an optimizationmodel was formulated to optimize the design variables using feasible direction method, and an optimization design of the railroad wagonwas achieved. Through sensitivity analysis, by updating the design variables, the car body structure was further optimized. Locomotivebody total weight reduced 7.44% after simulation optimization design, which has reached the design target.